The Relationship Between Student Learning Types and Indonesian Language Learning Achievement in FTIK IAIN Palopo Students - Firman Firman; Mirnawati Mirnawati; Sukirman Sukirman; Nurul Aswar (P3I Luwu Raya, 2020)
This study aims to determine the type of learning, achievement and the relationship between the type of learning and student achievement in FTIK IAIN PAlopo students. The population in this study were all students and lecturers of FTIK IAIN Palopo. For this reason, the